2013
DOI: 10.1172/jci63748
|View full text |Cite
|
Sign up to set email alerts
|

Tumor fibroblast–derived epiregulin promotes growth of colitis-associated neoplasms through ERK

Abstract: Molecular mechanisms specific to colitis-associated cancers have been poorly characterized. Using comparative whole-genome expression profiling, we observed differential expression of epiregulin (EREG) in mouse models of colitis-associated, but not sporadic, colorectal cancer. Similarly, EREG expression was significantly upregulated in cohorts of patients with colitis-associated cancer. Furthermore, tumor-associated fibroblasts were identified as a major source of EREG in colitis-associated neoplasms. Function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
96
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 53 publications
4
96
2
1
Order By: Relevance
“…12 CAF-derived epiregulin is proposed to be crucially involved in AOM/DSS-induced neoplasms by activating mitogen-activated protein kinase (MAPK) pathway. 13 However, we failed to observe a sustained elevation of epiregulin and the effects of CCL3 or CCR5 deficiency on its expression in colon. On the contrary, HB-EGF expression was markedly attenuated in CCL3-or CCR5-deficient mice, implying that the CCL3-CCR5 axis can regulate HB-EGF expression by fibroblasts in colon.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…12 CAF-derived epiregulin is proposed to be crucially involved in AOM/DSS-induced neoplasms by activating mitogen-activated protein kinase (MAPK) pathway. 13 However, we failed to observe a sustained elevation of epiregulin and the effects of CCL3 or CCR5 deficiency on its expression in colon. On the contrary, HB-EGF expression was markedly attenuated in CCL3-or CCR5-deficient mice, implying that the CCL3-CCR5 axis can regulate HB-EGF expression by fibroblasts in colon.…”
Section: Discussionmentioning
confidence: 60%
“…11 In the AOM/DSS-induced CAC model, the contribution of CAF-derived growth factors has been documented. 12,13 However, the mechanism regulating CAF trafficking in AOM/DSS-induced CAC remains unclear. We observed that AOM/DSS treatment enhanced the intracolonic expression of another chemokine, CCL3, which can exhibit biological effects on leukocytes and non-leukocyte cells, particularly fibroblasts.…”
mentioning
confidence: 99%
“…Because Areg and Ereg are both ADAM17 substrates (53), it has been postulated that ADAM17-mediated ErbB ligand shedding to produce soluble ligands plays critical role in activating ErbB signaling in IECs (21). Although the cellular source of these ErbB ligands was not clearly defined in this study, other studies have highlighted the contribution of ErbB ligand/EGFR signaling axis from nonepithelial mucosal cell types, including myeloid/ immune cells and pericryptal myofibroblasts found in the lamina propria (54,55).…”
Section: Discussionmentioning
confidence: 81%
“…Epithelia were purified (35) and immunoblots performed (36) with antibodies against Cosmc (C4; Santa Cruz) and actin (H-10; Santa Cruz).…”
Section: Methodsmentioning
confidence: 99%
“…Intestinal epithelia were purified (35) and total RNA isolated by RNeasy (Qiagen) with RNA quality and purity assessed by Agilent BioAnalyzer and nanodrop, respectively. University of California, Los Angeles (UCLA) genomics core performed RNA amplification and hybridization on Illumina mouse ref 8 v2.0 expression chips.…”
Section: Methodsmentioning
confidence: 99%